Impact of epidemiological and psychosocial factors on blood pressure control - Lázaro Pablo Linares Cánovas; Guillermo Luís Herrera Miranda; Liyansis Bárbara Linares Cánovas; Rubén Dario Lemus Ramos; Adalina Cánovas Linares Montano; Wiliam Ismel Sánchez Muñoz; Geovani López Ortiz (Revista Cubana de Medicina Militar)
Introduction: The lack of blood pressure control motivates an adequate study of related epidemiological and psychosocial characteristics.